Gabapentin versus Transdermal Fentanyl Matrix for the Alleviation of Chronic Neuropathic Pain of Radicular Origin: A Randomized Blind Multicentered Parallel-Group Noninferiority Trial - Chang Ju Hwang; Jae Hyup Lee; Jung-Hoon Kim; Sang Hyuk Min; Kun-Woo Park; Hyoung-Yeon Seo; Kwang-Sup Song (Pain Research and Management)
A number of studies have been published proposing various approaches to the treatment of neuropathic pain; however, to our knowledge, no attempts have been made to compare gabapentin and fentanyl in patients with lumbar radiculopathy. We evaluated the relative efficacy and safety of fentanyl matrix and gabapentin for the treatment of chronic neuropathic pain of radicular origin. The study was designed as a randomized blind multicentered parallel-group noninferiority trial. A total of 108 patients with moderate-to-severe pain (≥4 intensity on an 11-point numeric rating scale) were randomly prescribed either fentanyl matrix or gabapentin over a period of 56 days. In the primary analysis, the noninferiority of fentanyl matrix treatment was evaluated in relation to the efficacy of gabapentin based on the pain intensity difference (PID) at 56 days after the first dose of the drugs. Secondary endpoints included pain relief, improvement in functional status (the Korean-Oswestry Disability Index (K-ODI)), improvement in depressive symptoms (Korean-Beck Depression Index (K-BDI)) between the 28th and 56th day, and adverse events (AEs). Analysis of the primary efficacy endpoint established the noninferiority of fentanyl matrix compared with gabapentin, with no statistically significant difference observed in the PID after 56 days for the two treatment groups. Similarly, analysis of pain relief revealed no significant differences between the groups on days 28 and 56. There was no difference in the K-ODI and K-BDI between the groups during the study period. The overall incidence of at least one AE was similar for fentanyl matrix (67.3%) and gabapentin (69.6%). The most commonly reported AEs for patients treated with fentanyl matrix and gabapentin included dizziness (30.8% vs. 44.6%, respectively), somnolence (26.9% vs. 35.7%), and constipation (15.4% vs. 17.9%). This study demonstrated that the analgesic effect of fentanyl matrix is noninferior in comparison with gabapentin and supports the use of fentanyl matrix as an effective and safe treatment for moderate-to-severe chronic neuropathic pain. This trial is registered with NCT01127100.